POST-MILLENIAL STUDENTS’ ATTITUDES TOWARDS THE ONLINE SEARCH ENGINE IN EFL LEARNING - Angela Bayu Pertama Sari; Sri Rejeki (Premise: Journal of English Education and Applied Linguistics, 2019)
This research attempted to depict teachers' perspectives towards the post-millennial students' attitudes on using the online search engine in EFL learning. The research employed descriptive-interpretative qualitative research. 12 English teachers of the non-English major students were purposefully selected to be the subject of the research. The findings of the research pointed out that students' who were categorized as post-millennial generation used online search engine a lot in EFL learning. The findings showed that some negative attitudes occurred in EFL learning regarding the usage of the online search engine. The two most prominent ones were the act of plagiarism and being lazy due to the access to instant information. Despite it all, the results showed that the students’ positive attitude towards online search engine was more significant than the negative ones. Furthermore, the other research findings also illustrated that the EFL learning activities that were interfered by the online search engine at most is writing. Then, Google is the most used online search engine by the EFL post-millennial students.